Economic Recovery after the Covid 19 Pandemic of Utilization of Village-Owned Enterprises in Indonesia - Laksana, RIO Dhani; Adi, Pramono Hari; suwandari, Lusi (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2023)
The results of this study concluded that: 1) Village income during the COVID-19 pandemic decreased due to limited community activities outside the home and reduced public spending. The decline in income from large events such as weddings and celebrations caused the rent for tents and other Bumdes income to decline. 2) The village party is now using a marketing strategy where activities outside the home such as the opening of the market and the community can return to their activities outside the home on the condition that they comply with the protocols set by the government such as keeping a distance and wearing masks. 3) The results of declining income during the covid pandemic Village-Owned Enterprises affect the level of community welfare with the income they get. 4) BUMDes besides being able to improve public services and optimize village assets, also play a role in supporting, facilitating, and coordinating the productive economic efforts of rural communities. BUMDes can be the parent of ecotourism activities or village ecotourism. BUMDes plays an important role in providing convenience services in saving and borrowing small-scale business capital for productive businesses of rural communities in collaboration with external parties (both banks and private companies).